(untitled) (EAAE Annual Conference Proceedings, 2023)
This paper explores creative labour production in architectural design studios (in Brazil, UK and Italy). In contrast to narratives of free autonomy, participant observation revealed conflicting mechanisms, such as: subjectification, distinction, and hierarchical expropriation. This is pivotal in a transition period where architecture confronts the myths of geniuses aiming for paradigms of knowledge exchange and inclusion.